2009
DOI: 10.1126/science.1163806
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of HipA-Mediated Multidrug Tolerance and Its Neutralization by HipB

Abstract: Summary Bacterial multidrug tolerance is largely responsible for the inability of antibiotics to eradicate infections and is caused by a small population of dormant bacteria called persisters. HipA is a critical Escherichia coli persistence factor that is normally neutralized by HipB, a transcription repressor, which also regulates hipBA expression. Here we report multiple structures of HipA and a HipA-HipB-DNA complex. HipA has a eukaryotic Ser/Thr kinase-like fold and can phosphorylate the translation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
372
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(383 citation statements)
references
References 31 publications
8
372
2
1
Order By: Relevance
“…The toxin components of the TA modules exert their effects in different ways by targeting essential cellular functions such as DNA replication, protein synthesis, cell division, peptidoglycan biosynthesis and ribosome assembly; however, RNA cleavage is the most prevalent mode of action [10][11][12][13][14][15][16] . These ribonucleases cleave RNA in either a ribosome-dependent (for example, RelE, HigB and YoeB) or ribosome-independent manner (for example, MazF, ToxN and VapC) 17,18 .…”
mentioning
confidence: 99%
“…The toxin components of the TA modules exert their effects in different ways by targeting essential cellular functions such as DNA replication, protein synthesis, cell division, peptidoglycan biosynthesis and ribosome assembly; however, RNA cleavage is the most prevalent mode of action [10][11][12][13][14][15][16] . These ribonucleases cleave RNA in either a ribosome-dependent (for example, RelE, HigB and YoeB) or ribosome-independent manner (for example, MazF, ToxN and VapC) 17,18 .…”
mentioning
confidence: 99%
“…3B). This Lys is not commonly present in canonical kinases but is found in HipA and CtkA, two bacterial kinases that are remotely related to the Fam20 family (7,35,36).…”
Section: Resultsmentioning
confidence: 99%
“…However, how HipA mediates growth arrest is still unknown. It was found that HipA may phosphorylate elongation factor EF-tu (27), but HipA overexpression has been shown to arrest both translation and transcription (23), suggesting other targets for HipA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm that the hipBA TA module plays a key role in determining bacterial persistence. However, even though the structure of the HipBA complex is known (27) and growth arrest is shown to be due to HipA toxicity, any account of persistence must include an explanation of phenotypic variability: How does the coexistence of two distinct growth phenotypes within a genetically uniform population come about?…”
mentioning
confidence: 99%